Relationships between satisfaction of Muslim women on financial supports after divorce and ex-husbands' compliance to the supports with post-divorce welfare - Hasbullah @ Abdullah, Muslihah; Mohd Zin, Najibah; Wok, Saodah (Universiti Putra Malaysia Press, 2009)
The main objective of this study was to assess the welfare of divorced women in relation to financial supports after divorce, i.e. iddah maintenance, mut’ah, arrears of maintenance, and child maintenance. The specific objectives were to determine the divorced women’s satisfaction with the amount of financial supports, the ex-husbands’ compliance to court-ordered financial supports, their satisfaction with post-divorce welfare (levels of economic strain and depression), the relationships between satisfaction with the amount of financial supports and post-divorce welfare, as well as the relationships between ex-husbands’ compliance to court-ordered financial supports and post-divorce welfare. Data were collected using a questionnaire. The sample comprised of 201 divorced women selected from the cases recorded in the year 2003 till 2005 at the Shariah Subordinate Courts of Hulu Langat and Gombak Timur, Selangor. Pearson correlation showed that two factors were negatively correlated with the economic welfare of the divorced women, i.e. the dissatisfaction with the amount of iddah maintenance, mut’ah, and child maintenance and the ex-husbands’ none or partial compliance to the court-ordered iddah maintenance, mut’ah, and child maintenance. However, on the contrary to the expectation, the divorced women’s satisfaction with the amount of all types of financial supports provided by the ex-husbands and their ex-husbands’ none or partial compliance to all types of financial supports was found to have no significant relationships with depression. The findings also indicated that the assessment of a reasonable sum of financial supports and the effective enforcement of court order were significant factors that might augment the welfare of women after divorce.